Current Situation Analysis and Adaptability Research of Fracturing-flooding for Low Permeability Reservoir - Liu, Shaoqing; Hou, Wenlong; Wang, Zhiyuan (International Journal of Electric Power and Energy Studies, 2024)
Pressure drive technology has been widely applied in the enhanced oil recovery of low permeability reservoirs in recent years. This technology improves the oil-water connectivity by injecting working fluid, effectively displacing crude oil. This paper discusses the mechanisms of pressure drive technology and its applications in selecting wells and layers, well pattern design, and optimizing well spacing. It is found that the diamond anti-nine-point pattern is the most effective in early-stage oil recovery, while the rectangular anti-five-point pattern is suitable for later-stage development. In addition, the optimization of injection volume and rate, as well as the combination of various monitoring techniques, is crucial for enhancing pressure drive effectiveness. The study also proposes key indicators for evaluating the adaptability of pressure drive, which can guide the efficient development of low-permeability reservoirs.